THE RELATIONSHIP BETWEEN DEMOCRATIC PARENTING PATTERN OF PARENTS AND SELF-EFFICIENCY WITH STUDENTS' LEARNING MOTIVATION OF SMPIT AL HIJRAH DELI SERDANG SEA - Deli Yanti Rambe; Risydah Fadhilah; Nefi Darmayanti (RADJA PUBLIKA, 2023)
The purpose of this study was to determine the relationship between parents' democratic parenting and learning motivation in students at SMPIT Al Hijrah Laut Dendang Deli Serdang. To determine the relationship between self-efficacy and motivation to learn in students. To find out the relationship between parents' democratic parenting and self-efficacy with learning motivation in students of SMPIT Al Hijrah Laut Dendang Deli Serdang. This research is a quantitative study with a correlational approach between two independent variables, namely democratic parenting parents (X1) and self-efficacy (X2) with the dependent variable namely learning motivation (Y). The research was conducted at SMPIT Al Hijrah, Transportation Road, Dendang Sea, Deli Serdang, North Sumatra. The population in this study were all students of SMPIT Al Hijrah Laut Dendang. Deli Serdang totaled 137 students and there were 8 (eight) classes and a sample of 137 students to be used as research subjects. The data collection method in this study was carried out using the measuring scale method. which uses a list of questions or statements that must be answered or a list of fields that must be filled in by a number of subjects in order to express the conditions one wants to know. This study used the statistical program SPSS 25 for windows, data analysis techniques using Multiple Regression Analysis, Hypothesis Testing, Classical Assumption Testing, Normality Testing and Linearity Testing. which uses a list of questions or statements that must be answered or a list of fields that must be filled in by a number of subjects in order to express the conditions one wants to know.